Constelaciones organizacionales (2019)
This document, evidences documentary information about the COs organizational Constellations, is a systemic tool for help in the solution of problems in organizations. The systematic principles of the organization are presented, such as the right to belong, order and the balance between giving and taking, maintaining a stable and healthy organization. Organizational constellations present new tools for the understanding, analysis and management of any situation supporting organizational development.